The probability analysis of ejecta particles damaging a spacecraft operating around asteroids after an artificial impact experiment: Hayabusa 2 ’s SCI operation safety study - Soldini, Stefania; Saiki , Takanao; Tsuda , Yuichi (Frontiers in Space Technologies, 2022)
On April 5th, 2019, the Hayabusa 2 spacecraft performed the first successful artificial impact experiment on an asteroid. The Small Carry-on Impactor (SCI) device was deployed at 500 m of altitude above Ryugu's surface. The 2 kg copper projectile hit Ryugu's surface in 40 minutes and caused the formation of a 14.5 m in diameter artificial crater. Once the SCI was deployed, the Hayabusa 2 spacecraft performed a two-week escape trajectory reaching altitudes as far as 120 km from Ryugu. The spacecraft returned then to its nominal position at 20 km altitude (Home-Position) from Ryugu for hovering control. This was done to prevent ejecta particles seriously damaging the spacecraft and compromise its functionality. In this article, we present a method to forecast the daily probability of spacecraft damage along the selected nominal escape trajectory due to the debris cloud formed by an artificial impact. The result of the damage analysis confirmed that the selected escape trajectory experienced a small number of particle collisions under the design threshold, which would not have resulted in damage. Indeed, no damage was reported on the Hayabusa 2 spacecraft and it kept operating nominally after the SCI operation. The method here presented serves as guideline for post-impact mission operations to forecast and estimate the probability of damage on spacecraft or cubesats operating near a small celestial body after an artificial impact experiment has occurred.